SMIIC Forum 2012 (American Journal of Islam and Society, 2013)
Organized by the Standards and Metrology Institute for Islamic Countries(SMIIC), a subsidiary organ of the Organization of Islamic Cooperation(OIC), this forum was held on November 6-9, 2012, at Turkey’s Cornelia DeLuxe Resort in Belek. The 160 delegates, who came from thirty-five countries,represented the National Standardisation Bodies (NSB), important nationalorganizations of member countries, and such international organizationsas the International Organisation for Standardisation (ISO), the InternationalElectrotechnical Commission (IEC), the European Committee forElectrotechnical Standardisation (CENELEC), the Standardisation Organisationfor the Cooperation Council for the Arab States of the Gulf (GSO),the Turkish Standards Institution (TSE), the Turkish Accreditation Agency(TURKAK), the Saudi Standards Metrology and Quality Organization(SASO), the Malaysian National Metrology Laboratory (SIRIM), the InternationalLaboratory Accreditation Cooperation (ILAC), the OIC GeneralSecretariat, the Commercial Cooperation of the Organization of Islamic Cooperation(COMCEC), the Statistical Economic and Social Research andTraining Centre (SESRIC), and the Islamic Centre for the Development ofTrade (ICDT).Also present were media outlets, representatives of various governmentbodies, officers from the Presidency of Religious Affairs of the Republic ofTurkey (DIYANET), and academics from significant international universities.One of the forum’s main objectives was to create a platform to bring togetherexperts and professionals from the fields of standardization, accreditation, andmetrology in order to discuss these areas’ current circumstances within OICmember countries and at the international level ...